From mai–juin '68 to Nuit Debout: shifting perspectives on France's anti-police. (3rd April 2018) - Reynolds, Chris
Abstract: In the great drama that was mai – juin 1968, the police were unquestionably a central actor. In particular, they played a pivotal role in transforming what started out as a relatively minor, student-based rebellion into a nationwide movement that brought the Gaullist regime to the brink of collapse. The 2016 Nuit Debout protest movement drew strong comparisons to the 1968 events, with many wondering whether France stood to experience a repeat of those heady days. This article will argue that the inability of Nuit Debout to capture the imagination of the general public in a similar fashion to what happened in 1968 is not solely the result of the exceptional and divergent contexts. Instead, it will contend that this failure is also to be understood through an appreciation of shifting perspectives on France's anti-police. Such positive developments, it will be argued, have ironically been shaped as a result of the 1968 events and the manner in which they are most commonly remembered.